Multimodal Hand Hygiene Improvement Strategy Meningkatkan Kepatuhan Cuci Tangan Five Moment - maryana, maryana; Anggraini, Rima Berti (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
Nurses can be a source of nosocomial infections in hospital. Nurse’s Hand Hygiene is most important step to reduce infection. The study aims to export the multimodal Hand Hygiene improvement strategy as a solution for PPI managers in increasing nurses handwashing compliance according to standards in hospitals. This research uses an observational pilot studi approach. The room used as a pilot study was a pediatric nursing room which consisted of 12 implementing nurses, 1 specialist doctor, and 1 assistant doctor. The results showed that the hand washing compliance of nurses’ increased to 80% after implementation of the Multimodal Hand Hygiene Improvement Strategy. The conlusion. nurses’ hand washing compliance is classified as obedient after the Multimodal Hand Hygiene Improvement Strategy is carried out. It is recommended that the Multimodal Hand Hygiene Improvement Strategy can be used as an approach to improve Five Moment Hand Hygiene compliance in hospitals.